Challenges of Older Adults in India: A Qualitative Study of Institutional Care, Preferences and Government Initiatives - K Annapuranam (Research on Ageing and Social Policy)
This qualitative study examines the challenges of older adults in India, with a special focus on their preference for institutional care over familial support. As demographic shifts occur, understanding the reasons for the choice of care is crucial. In-depth interviews conducted with fifteen older adults, mostly retired government officials, reveal that many opted for institutional care as a result of negligence, disregard, and abuse by family members. When it comes to the choice of institutional care, other factors such as safety, tranquillity, and proper care are strongly influenced. On the other hand, cultural factors, including changing family dynamics and societal attitudes towards ageing, further complicate the caregiving landscape. Therefore, the study emphasizes the urgent need for legislative measures to address the growing dependency ratio of older adults and ensure that they remain healthy and productive. Moreover, the study acknowledges its shortcomings, such as a narrow focus on economically self-sufficient older adults and the exclusion of family perspectives, which might have offered a more comprehensive understanding of care choices. Overall, this study underscores the importance of creating supportive environments for older adults that assist them and promote their well-being in light of changing social norms and expectations.